A quasi 2D semianalytical model for the potential profile in hetero and homojunction tunnel FETs. (November 2015) - Villani, F.; Gnani, E.; Gnudi, A.; Reggiani, S.; Baccarani, G.
Abstract: A quasi 2D semianalytical model for the potential profile in hetero and homojunction tunnel FETs is developed and compared with full-quantum simulation results. It will be shown that the pure analytical solution perfectly matches results at high V DS . However, a coupling with the numerical solution of the 1D Poisson equation in the radial direction is necessary at low V DS, in order to properly account for the charge density in equilibrium with the drain contact. With such an approach we are able to correctly predict the potential profile for both the linear and saturation regimes.